Marius, A Short Guide to Writing About History. Brundage, Going to the Sources - A Guide to Historical Research and Writing - Pease, Arthur (Teaching History: A Journal of Methods, 1991)
Overheard in the hallway outside of 201 Murkland - Susan: “I heard we would have to do a lot of writing in this course but an essay, a book review and a paper! The prof either has a lot of time on her hands or she hates her grad assistant.” Sam: “Yes, Susan, you are going to have to work for a change. But, Dr. Wright did tell us about a couple of very useful books on historical research and writing. Let's head to the bookstore and check them out.” Would that we all had more Sams than Susans in our classes but we can at least hope that Susan follows Sam's advice and does "check out" these books.